Management and Outcome of Bowel Injury Following Blunt Abdominal Trauma; Our Experience in the Department of Casualty and General Surgery in Dhaka Medical College, Dhaka - Habib, Md Ahsan; Ar Rashid, Muhammad Harun; Naznin, Kazi Nasid; Rahman, Mohammad Zillur; Afrin, Tangina; Parveen, Farzana (Sir Salimullah Medical College Journal, 2022)
Background: Blunt abdominal injury is common in trauma patients. Evaluation of patients who have sustained blunt abdominal trauma may pose a formidable problem and significant intra-abdominal injury is one of the most difficult problems faced by emergency physician and trauma surgeon in the management of trauma. Traumatic bowel injury is one of the curable traumatic conditions . An accurate and timely diagnosis and treatment give an excellent out come in most of the cases . A delay in diagnosis has been shown to be associated with significant morbidity and mortality. Objective: The purpose of the study was to evaluate the different management options and the outcome of management of bowel injury following blunt abdominal trauma. Methodology: This is a randomized clinical trial conducted over a period between July 2015 to June 2017 carried out in the Department of Casualty and General Surgery in Dhaka Medical College. Consecutive 100 patients with blunt abdominal trauma with irrespective of the age and gender were selected as study population. Results: Among the 100 cases included in the study shows outcome of the management was quite acceptable with 46% of patients having uneventful recovery. The major morbidity was related to abdominal wound and infective complications . 14% of patients had wound infection , 6% had wound dehiscence, 3% had intra-abdominal abscess, 1% had anastomotic leakage and 2 patients developed enterocutaneous fistula. Conclusion: Traumatic bowel injury is one of the commonest traumatic conditions that are encountered in the hospitals, namely in the department of Casualty surgery.It is evident from different studies that certain factors like prolonged transportation time , delay in receiving definitive surgical treatment, failure to receive early resuscitation with consequent poor hemodynamic status etc. have been associated with a poor outcome in the management of such cases. Sir Salimullah Med Coll J 2021; 29(2): 147-152